Introducing the Foveola lunata, an anatomical landmark of the wrist - Wozniak, Slawomir; Paulsen, Friedrich (Annals of Anatomy-Anatomischer Anzeiger, 2023)
The lunate foveola is often the starting point of a cystic swelling called a "ganglion". To make the anatomy of this region more relevant to the needs of clinicians and more accessible to students, we propose to introduce the term lunate foveola (Foveola lunata) on the dorsal side of the wrist just distal to the os lunatum. The easily located foveola will help in the examination of the wrist to more easily understand the anatomy of the wrist and facilitate the examination of patients with wrist injuries when an injury to the lunate (Os lunatum) is suspected.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Carpal bones; Lunate foveola; Lunate injury; Perilunate dislocation; Wrist